Epitaxial YBa2Cu3O7−x nanocomposite films and coated conductors from BaMO3 (M = Zr, Hf) colloidal solutions. (22nd February 2018) - Obradors, X; Puig, T; Li, Z; Pop, C; Mundet, B; Chamorro, N; Vallés, F; Coll, M; Ricart, S; Vallejo, B; Pino, F; Palau, A; et al.
Abstract: Superconducting nanocomposites are the best material choice to address the performance required in power applications and magnets working under high magnetic fields. However, it is still challenging to sort out how to achieve the highest superconducting performance using attractive and competitive manufacturing processes. Colloidal solutions have been recently developed as a novel and very promising low cost route to manufacture nanocomposite coated conductors. Well dispersed and stabilized preformance nanoparticle solutions are first prepared with high concentrations and then mixed with the YBa2 Cu3 O7 metalorganic precursor solutions to generate colloidal solutions to grow the nanocomposite films. Here we demonstrate, for the first time, that non-reactive BaZrO3 and BaHfO3 perovskite preformed nanoparticles are suitable for growing high quality thin and thick films, and coated conductors with a homogeneous distribution and controlled particle size using this fabrication method. Additionally, we extend the nanoparticle content of the nanocomposites up to 20%–25% mol without any degradation of the superconducting properties. Thick nanocomposite films, up to 0.8 μ m, have been prepared with a single deposition of low-fluorine solutions using an ink jet printing dispenser and we demonstrate that the preformed nanoparticles display only a very limited coarsening during the growth process and so high critical current densities J c ( B ) under high magnetic fields. These films show the highest critical currents achieved so far based on the colloidal solution approach, I c = 220 A/cm-w at 77 K and self-field, and they still have a high potential for further increase in the film thickness. Finally, we also show that nanocomposite YBa2 Cu3 O7 –BaZrO3 coated conductors based on an alternating beam assisted deposited YSZ buffer layer on stainless steel metallic substrates can be developed based on these novel colloidal solutions. Non-reactive preformed oxide perovskite nanoparticles are therefore very promising elements to further advance the colloidal solution approach in the implementation of low cost and high performance coated conductors for high magnetic field applications.